DEVELOPMENT OF SOFTWARE AND HARDWARE FOR A SMART HOME SYSTEM - Луценко, Татьяна; Астафьева, Александра; Коваленко, Иван; Берков, Юрий (SWorldJournal, 2021)
The paper considers the methods and purpose of creating a system for combining most types of smart home sensors into one system, and the ability to control the system via the Internet. The main types of sensor connection are considered. Selected technolog